Lecturers' Communication Strategies for Developing Pancasila-Based Student Character at STAI Tebing Tinggi Deli - Muhammad Idris; Fauji Wikanda; Dedi Sahputra (MASI Mandiri Edukasi, 2026)
This study aims to analyze the effect of lecturers' communication strategies on the development of students' character based on Pancasila at STAI Tebing Tinggi Deli and to explain how these communication strategies are implemented in the learning process. The study uses a mixed methods approach with an explanatory sequential design. Quantitative data were collected through questionnaires distributed to students and analyzed using descriptive statistics and simple linear regression. Qualitative data were collected through in-depth interviews, observations, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that lecturers' communication strategies have a positive and significant effect on the development of students' character based on Pancasila (β = 0.718; p < 0.001) with a contribution of 51.6%. Role modeling is the most dominant communication strategy, while digital communication hasn't been used optimally yet. The qualitative findings show that humanistic interpersonal communication, contextual persuasive communication, dialogic and participatory learning, providing constructive feedback, and lecturers' role modeling can strengthen students' religiosity, integrity, responsibility, tolerance, cooperation, and appreciation of diversity. The success of these strategies is supported by a religious academic culture, harmonious interpersonal relationships, institutional commitment, as well as academic and student activities, even though there are still challenges like low student participation, the influence of digital media, limited learning time, and students' different backgrounds. This study concludes that lecturers' communication strategies are an important factor in developing students' character based on Pancasila.